Relationship of constipation and autonomic neuropathy in patients with non-insulin dependent diabetes mellitus and the effects of cisapride on colonic transit time - M. Emin ÖNDE,; A. Kemal GÜRBÜZ,; Levent DEMİRTÜRK,; Ergun KOÇER,; Mesut BAŞAK,; Hayati TOR, (Turkish Journal of Gastroenterology, 2019)
-